Synergy of Public Policy and Community Participation in Stunting Prevention Efforts in Kelurahan Keputih, Surabaya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Stunting remains a critical public health issue in Indonesia, with national prevalence reaching 21.6% in 2022, including 19.8% in East Java and 20.7% in Surabaya. In Kelurahan Keputih, stunting is strongly associated with household vulnerability, limited health literacy, and inadequate access to integrated health services. This study aims to analyze the synergy between public policy and community participation in stunting prevention, emphasizing the role of collaborative governance in fostering sustainable interventions. A qualitative case study design was employed, combining policy document analysis, in-depth interviews with local officials, health workers, and community leaders, as well as field observations. Thematic analysis revealed that while national and municipal policies provide a robust structural framework, their effectiveness at the local level is determined by grassroots engagement. Community participation—particularly through posyandu activities, maternal nutrition programs, and participatory health education—was found to significantly improve program adaptability and sustainability. The findings further demonstrate that synergy between policy and community efforts not only enhances social trust and health awareness but also ensures more equitable access to resources. Practically, the study highlights that integrating bottom-up community ownership into top-down frameworks can accelerate stunting reduction, offering a replicable model of collaborative governance for other urban areas confronting similar health disparities.